Modernisms in Minas Gerais: Tradition, Nationalism, and Regionalism in the Periodicals A Revista (Belo Horizonte, 1925–1926) and Verde (Cataguases, 1927–1928; 1929) (Ágora Journal, 2025)
From the perspective of the plural construction of the modernist movement, not limited by geography or temporality, the theme gains complexity in the different visions revealed by the groups involved, especially through the debates published in their magazines, which conveyed their own interpretations of what is modern or modernist, depending on their position within the modernist network. In Minas Gerais, two periodicals stand out as representative expressions of modernism in the state during the 1920s: A Revista, from the capital, Belo Horizonte, and Verde, from the small town of Cataguases in the Minas Gerais countryside. From the apparent contradiction of being modern in an environment deeply rooted in its colonial past, the study questions the particularities of both groups’ projects in dialogue with the broader debates undertaken by other intellectuals and magazines. As a guiding thread of analysis, three recurring themes present in both periodicals were selected: tradition, nationalism, and regionalism, which will be examined in two stages—first, in the opening manifestos that launched the publications, and then in the content developed throughout their pages.
Keywords: Modernism; Periodicals from Minas Gerais; Tradition; Nationalism; Regionalism.